Manejo de cicatrices patológicas excesivas en el Servicio de Rehabilitación - Cerda A., Lorena; Villanueva C., Valeria; Román Q., América; Contreras A., Josefina (Revista Hospital Clínico Universidad de Chile, 2018)
The excessive pathological scars are subdivided into hypertrophic, keloid and contracted. They have a complex pathophysiology, not entirely known that only exists in humans. Although the frequency of presentation is not high, excessive pathological scars can affect several areas of human functioning, in the first level of functions and body structures and in the second level of activities of daily life and participation. The evaluation of patients must be complete, including the scar, and any other affected body system, together with psychological, functional and socioeconomic factors. In the treatment of excessive scars there are multiple options that must be combined for a better result. The non-surgical treatments of the most used scars are the pressotherapy, silicone plates, intralesional injections and laser. There are other rehabilitation treatments that although without solid evidence could have a role in patients. The referral to the rehabilitation service is recommended for patients with excessive pathological scars located in areas of folds or special areas and / or, which are accompanied by pain, alterations in the function of the body segment or limitations in activities of daily life, for comprehensive assessment and multidisciplinary management.